Eriugena Unbound Cover eBook
This volume contains ten articles dedicated to the comparative study of emotions in literature, addressing emotions relating to ‘Fringes’ in both Old English and Old Norse-Icelandic literature, but also consider historical accounts, correspondences, and epic poetry from Late Antiquity to the Early Modern Period.